2018
DOI: 10.7717/peerj.5832
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of antimicrobial activities and fatty acid composition of actinobacteria isolated from water surface of underground lakes from Badzheyskaya and Okhotnichya caves in Siberia

Abstract: Extreme and unusual ecosystems such as isolated ancient caves are considered as potential tools for the discovery of novel natural products with biological activities. Actinobacteria that inhabit these unusual ecosystems are examined as a promising source for the development of new drugs. In this study we focused on the preliminary estimation of fatty acid composition and antibacterial properties of culturable actinobacteria isolated from water surface of underground lakes located in Badzheyskaya and Okhotnich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…With the increasing threat to patients of antibiotic resistance, the need for novel antibiotics has become a very serious issue. Researchers have expanded their search to many different environments, including bat caves [ 26 ], underground lakes [ 27 ], and deserts [ 28 ], with the aim of finding new candidate antibiotics. In this study, we screened water samples from a drinking pipe and found a Streptomyces , YX44, that exhibited promising broad-spectrum inhibition activity against a number of different pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing threat to patients of antibiotic resistance, the need for novel antibiotics has become a very serious issue. Researchers have expanded their search to many different environments, including bat caves [ 26 ], underground lakes [ 27 ], and deserts [ 28 ], with the aim of finding new candidate antibiotics. In this study, we screened water samples from a drinking pipe and found a Streptomyces , YX44, that exhibited promising broad-spectrum inhibition activity against a number of different pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…http://www.evrogen.com ). PCR was performed in a T-Gradient thermocycler (Biometra, Germany) in the volume of 25 μ L. The PCR parameters were as follows: initial denaturation at 95°C for 5 min, followed by 25 cycles of 95°C for 40 sec, 49–52°C for 25 sec, and 72°C for 110 sec, and final elongation at 72°C for 5 min [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…e PCR parameters were as follows: initial denaturation at 95°C for 5 min, followed by 25 cycles of 95°C for 40 sec, 49-52°C for 25 sec, and 72°C for 110 sec, and final elongation at 72°C for 5 min [36].…”
Section: S Rrna Gene Sequencing and Phylogenetic Analysismentioning
confidence: 99%
“…One is the isolation of the organism and the subsequent assay of the antimicrobial activity of extracts against pathogenic bacteria. Numerous studies can be found in the literature, for which only a few representative papers are cited here [76][77][78][79][80][81]. In most papers, attempts to identify the bioactive compounds through chemical and structural analyses were not accomplished.…”
Section: Antibiotics From Subsurface Bacteriamentioning
confidence: 99%